Comparative performance of solar dryers for drying fruits - Shahrulnizamakmar, Bin Din (Universiti Malaysia Sarawak, UNIMAS, 2006)
This project is to study on an existing solar dryer and design to improve the performance of the dryer. The purpose of this prototype is to dry the bananas in three conditions which are not ripe, half ripe and ripe using natural convection and forced convection. The drying is done on direct sun light. then the performance of both dryers will be compared and the best efficient dryer will be determined.